Utilizing Network Pharmacology to Explore the Possible Mechanism of Coptidis Rhizoma in Kawasaki Disease - Fan, Xue; Guo, Xin; Li, Ying; Xu, Mingguo (Frontiers in Pediatrics, 2021)
Background: The purpose of the research is to identify the main active ingredients in Coptidis Rhizoma (CR) and explore the possible molecular mechanisms in the treatment of Kawasaki disease (KD). Material and Methods: A total of 58 children with KD were randomly divided into control group and Berberine treatment group. The therapeutic indicators of the 2 groups before and after treatments were compared. Then, compounds and drug targets of CR from the TCMSP, SWISS, SEA and the STITCH were collected, and targeted KD genes were retrieved from the DisGeNET, DrugBank and the GeneCards databases. The network pharmacology approach involved network construction, target prediction, and module analysis. GO and KEGG enrichment analysis were performed to investigate the possible pathways related to CR for KD treatments. Finally, protein expression was determined to verify the core targets using Western blotting in the cell experiment. Results: In total, 9 compounds, 369 relative drug targets and 624 KD target genes were collected in the above database. The network analysis revealed that 41 targets might be the therapeutic targets of CR on KD. GO and KEGG enrichment analysis revealed that the biological processes with response to hormone, response to inorganic substance and enzyme linked receptor protein signaling pathway, Pathways in cancer, Toll-like receptor signaling pathway and Pancreatic cancer as the most significantly, respectively. Protein expression of CASP3, PTGS2, SRC were up-regulated and AKT1 and ERK were down-regulated. Conclusions: We provided useful resource to understand the molecular mechanism and the potential targets for novel therapy of KD.